Effects of intrinsic aerobic capacity, aging and physical activity on interleukin-15 protein level in serum and skeletal muscle - Hyödynmaa, Juho (2015)
Myokines are cytokines and other peptides produced in muscle that can transmit autocrine, paracrine or endocrine signals to other tissues. This is a potential way for exercise to carry out its beneficial effects on different parts of the body. Interleukin-15 (IL-15) is a myokine that has been shown to exert beneficial effects on multiple tissues: skeletal muscle, adipose tissue, bone and skin. Muscle-derived IL-15 signaling remains to be fully elucidated. It is known that the expression and signaling is affected by aging, exercise, and intrinsic aerobic capacity. The purpose of this study was to assess the effects of intrinsic aerobic capacity, aging and physical activity separately and in combination on muscle and serum interleukin-15 protein levels in rats. Two rat strains were used: high capacity runner (HCR) and low capacity runner (LCR) rats, which have been selectively bred based on intrinsic running capacity. They were divided into 3 subgroups (n=10 per group): adult rats (HCR/LCR), old rats (HCR-o/LCR-o) and old rats with running wheel (HCR-oR/LCR-oR), for a total of 6 groups. IL-15 protein levels were measured from serum with ELISA and from three different muscles with western blot: gastrocnemius, soleus and extensor digitorum longus (EDL). The selected antibody produced two different signals in the western blot, assumed to represent two different isoforms of IL-15, and both were quantified. Voluntary running distance in runner groups was measured with a computerized recording system. The results of the present thesis show that IL-15 protein level was increased in the HCR strain compared to the LCR strain in the gastrocnemius (P=0.014) and EDL (P<0.001) for separate isoforms. IL-15 was increased in the serum (P=0.010), but reduced in the soleus (P=0.005) for one isoform with aging, whereas running was found not to have any significant effects. Univariate analyses also showed no combinatory effects of strain*age or strain*running. The main finding of this study was that intramuscular IL-15 protein was increased in the HCR compared to the LCR strain, as hypothesized based on unpublished microarray data. However, HCR rats did not show elevated IL-15 in serum. These results suggest that IL-15 action could be responsible in part for explaining some of the differences between HCR and LCR rats, such as oxidative properties of different muscles or abdominal fat.